Diversity, taxonomy and conservation of orchids in Peninsular Malaysia - Besi, Edward Entalai (2022)
As an attempt to examine the causes of forest disturbance and degradation of the orchid community, a comparative study on diversity and ecology in eight undisturbed (Padang 7, Bukit Rongkit, Taman Rimba Komanwel, Bukit Batu Kapal, Lata Kekabu, Lata Lawin, Lata Tanjung Kala, Bukit Pedu) and ten disturbed (Bukit Sekayu, Gunung Perlis, Bukit Batu Kapal, Tanah Merah, Hulu Setiu, Kuala Koh, Logging Bukit Batu Kapal, Bintang Hijau, Gawi, Petuang) forests in Peninsular Malaysia was conducted. The study reported 239 orchid species belonging to 65 genera, inclusive of not just the rare and endemic species, but also five new record species. Species richness, abundance, density and diversity of orchids varied across the localities. A higher density of orchids (2.433 plants/km2) occurred exclusively in the undisturbed forests than in the disturbed forests (0.228 plants/km2). As with the character of undisturbed forests, the temperature was between 27.8±0.3 oC and 31.2±0.2 oC, humid (77.1±1.2 %–89.6±0.9 %) and low light intensity (23.8±3.3 μmol m-2s-1–171.7±18.8 μmol m-2s-1) thus supporting the high density of the plants. Disturbed forests harboured higher diversity (H=4.934 and 1-D=0.990) and abundance (183 species of 57 genera) that determined to be highly influenced by the higher abundance of epiphytic orchids on the fallen trees and ease of accessibility in the logged forests. The lower diversity of orchids in the undisturbed forests supported by the higher dominance (D=0.015) of most abundant species. However, terrestrial and mycoheterotroph orchids were lower in density and abundance in the disturbed habitat indicating a gradual reduction in their niche availability following the disturbance. Also, the ecology data shows the microclimate conditions of the canopy-covered forest influenced by proximity to the logged area. Furthermore, the results show the composition of orchid communities in the undisturbed and disturbed forests associated with the host plant characteristics. Host types and bark texture preference were apparent for the epiphytic orchid species with certain types and textures hosting more orchid species than others. To further obtain an accurate estimate of the orchid floristic composition, integrative methods of macromorphology, micromorphology and molecular genetics are necessary to solve the taxonomic uncertainty and resolve species complexes at the infrageneric level. Floral micromorphology of three critically endangered Paphiopedilum were analysed concerning either infrageneric taxonomy or physioecological demands. Using scanning electron microscopy (SEM), surface of the dorsal sepal, synsepal, lateral petals, pouch or labellum, and staminode were investigated. Amongst the investigated features were epicuticular waxes, epicuticular ornamentation, trichome distribution and type, pustular glands, and papillae. The finding supports the distinction of P. barbatum from P. callosum var. sublaeve, which belong to subgenus Paphiopedilum, and from P. niveum, a species belonging to subgenus Brachypetalum, a separated monophyletic clade. From the physioecological view, the absence of glandular trichomes, and the low occurrence of papillae and stomata on the floral parts explain the unscented flowers of P. barbatum and P. callosum var. sublaeve. In this study, other than morphology, efficacy of the nuclear and chloroplast regions in discriminating the uncertain taxa of Dendrobium Sect. Calcarifera species were examined. For barcoding, nrITS, rbcL, matK, and psbAtrnH regions of 60 samples, including six samples of unknown identity, were sequenced except for D. corydaliflorum where only rbcL was reproducible. Amongst the single barcode regions, nrITS showed a high sequence quality (100%), high discriminatory power (99.7%), clear resolution of species in Maximum- Likelihood phylogenetic tree, and high congruence with the morphology data. Combined markers showed a high species resolution with the conspecific individuals all grouped together, especially any combinations with nrITS, due to the added sequence variation. Eighteen species were assessed using the internationally accepted IUCN criteria and categories. Of the 18 species, eight are classified as threatened (Endangered, Critically Endangered, or Vulnerable). Furthermore, 30 species are included in a poster on Endangered, Threatened and Rare Wild Orchids of Malaysia (Part 1 and 2) in collaboration with the Forestry Department of Peninsular Malaysia as an effort to increase awareness on the importance of orchid conservation between the public and the effectiveness of the current monitoring on illegal trade. The monitoring effort is now supported by DNA barcoding work which has so far included 74 entries for four barcode markers belonging to 43 endemic and rare species.